Correlation between bone mineral density, isokinetic peak torque and postural balance in postmenopausal women - Oliveira, Laís Campos de; Oliveira, Raphael Gonçalves de; Santos, Fabiano Cardoso dos; Júnior, Jorge Furtado de Campos; Santos, Géssika Castilho dos; Silva, Paula Roldão da; Silva, Jadson Marcio da; Sczepanski, Cláudia Roberta Brunnquell; Menossi, Berlis Ribeiro dos Santos; Martini, Fábio Antônio Néia; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Postmenopausal women typically present loss of bone mineral density (BMD), muscular strength, and postural balance. However, there is no consensus in the literature on the correlation between these variables. Objectives: Our objective was to verify the correlation between BMD, isokinetic peak torque of knee extensors and flexors, and static postural balance in postmenopausal women. Methods: Fifty-one postmenopausal women underwent BMD evaluation through dual-energy X-ray absorptiometry (DXA) for four bone regions (lumbar spine, femoral neck, total hip, and trochanter). Muscular strength of knee extensors and flexors was evaluated in an isokinetic dynamometer at 60 and 180 degrees per second in the dominant lower limb. Static postural balance was evaluated on a force platform during five different tasks (bipodal eyes open, bipodal eyes closed, semi-tandem eyes open, semi-tandem eyes closed, and unipodal). Statistical analysis involved Spearman’s correlation coefficient (rho). Results: There was no significant correlation between BMD and isokinetic peak torque of knee extensors and flexors. Approximately half (27 of 60) of the postural balance variables presented significant inverse correlations (p < 0.05) with BMD and of these, the majority (22 of 27) presented moderate correlation (rho between -0.49 and -0.30). Most correlations were for bipodal support tasks with eyes open and eyes closed. Conclusion: Greater postural oscillation in different balance tasks was correlated with lower BMD in postmenopausal women. Therefore, it is suggested that intervention protocols for women with impaired BMD, especially osteoporotic, consider balance training as part of rehabilitation.